2019
DOI: 10.1007/s00586-019-06243-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between radiographic parameters and spinopelvic muscles in adult spinal deformity patients

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
1
27
0
3
Order By: Relevance
“…Our findings are supported by previous investigations demonstrating relationships between alignment and FI of the lumbar PVM [9,10,15]. Lee et al compared eleven patients with lumbar flatback (average LL 11.6°) to ten volunteers, finding a significantly higher amount of FI throughout the lumbar PVM and psoas [10], leading the authors to conclude that muscular imbalance is likely related to the pathogenesis of the condition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are supported by previous investigations demonstrating relationships between alignment and FI of the lumbar PVM [9,10,15]. Lee et al compared eleven patients with lumbar flatback (average LL 11.6°) to ten volunteers, finding a significantly higher amount of FI throughout the lumbar PVM and psoas [10], leading the authors to conclude that muscular imbalance is likely related to the pathogenesis of the condition.…”
Section: Discussionsupporting
confidence: 91%
“…While the posterior vertebral musculature (PVM) is a key component of stabilization [9], its role in the pathogenesis of degenerative spine disease is unknown. Abnormal PVM has been demonstrated in patients with a variety of conditions, including low back pain, degenerative disc disease, and lumbar radiculopathy, and patients with degenerative lumbar scoliosis; investigators have shown asymmetry between musculature on opposite sides of the curve [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have highlighted the importance of the sagittal spine for pain and patient quality of life [2][3][4]. Trunk muscles have an important role in maintaining normal vertebral alignment and the stability of the spine [5]. Therefore, trunk muscles involved in lumbar-stabilization are at the forefront of research needs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has revealed that increased fat infiltration and decreased muscle volumes in trunk muscles are associated with sagittal malalignment in DSD patients [5], suggesting that trunk muscle dysfunction is related to DSD. Trunk muscles control balance and posture, which are essential for normal functional activities, e.g.…”
Section: Introductionmentioning
confidence: 99%